2019
DOI: 10.1212/wnl.0000000000006880
|View full text |Cite
|
Sign up to set email alerts
|

Electrically induced verbal perseveration

Abstract: ObjectiveThe present study aimed to elucidate the neural correlates of the deafferentation cognitive model of verbal perseveration (VP) by analyzing the connectomics of the sites where electric stimulation elicited VP during awake left glioma surgery.MethodsWe retrospectively reviewed the anatomic sites that generated VP when electrically stimulated in a series of 21 patients operated on while awake for a left glioma. Each stimulation point was manually located on the postoperative MRI and then registered to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…More specifically, the fact that left ATR and left UNC were more deteriorated in the subgroup of patients committing more errors agrees with studies showing that brain lesions and electrical stimulation of these tracts are involved in error commission. For instance, Han et al (2013) demonstrated an association of lesions in the left ATR and left UNC with semantic deficits, while Mandonnet et al (2019) showed that electrical stimulation of the striato-thalamic-cortical system, including the left ATR, evoked verbal perseverations. In addition, inclusion of the FAT in our study is notable, as this is a relatively new connective tract that is thought to have a key role in language ( Catani et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the fact that left ATR and left UNC were more deteriorated in the subgroup of patients committing more errors agrees with studies showing that brain lesions and electrical stimulation of these tracts are involved in error commission. For instance, Han et al (2013) demonstrated an association of lesions in the left ATR and left UNC with semantic deficits, while Mandonnet et al (2019) showed that electrical stimulation of the striato-thalamic-cortical system, including the left ATR, evoked verbal perseverations. In addition, inclusion of the FAT in our study is notable, as this is a relatively new connective tract that is thought to have a key role in language ( Catani et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common language interference found in this task is anomia, which is defined as the DESinduced phenomenon in which the patient is able to speak out the carrier phrase but unable to name the object (Sanai et al, 2008) or name with incorrect words. Other errors [e.g., perseveration (Duffau et al, 2005(Duffau et al, , 2008Gil Robles et al, 2005;Khan et al, 2014;Mandonnet et al, 2019b), hesitation (Hamberger et al, 2005), and tip-of-the-tongue (Hamberger et al, 2005)] are also reported in the literature. In addition, since speech output can also be assessed by this task, some researchers map speech arrest during picture naming instead of counting (Petrovich Brennan et al, 2007).…”
Section: Picture Namingmentioning
confidence: 83%
“…Compared to image sets found randomly from the Internet, usage of batteries and image sets with normative data available is more recommended. Duffau et al (2005); Mandonnet et al (2017Mandonnet et al ( , 2019b, and Rech et al (2019) select pictures from DO 80, which comprises of 80 black-and-white pictures with variables such as frequency, familiarity, and age of acquisition controlled. Some teams advocate the application of the Boston Naming test, which contains 60 line drawings with decreasing frequency.…”
Section: Picture Namingmentioning
confidence: 99%
“…Damage to the IFOF resulting in self-evaluation dysfunction may thus represent a critical insult in jargonaphasia, as it may not only impair error monitoring [2], but also prevent rehabilitation through correction [37]. Similarly, subcortical stimulation of the IFOF has been linked to verbal perseveration, an inappropriate repetition of a previously pronounced word or phoneme [38]. Perseveration is considered a hallmark feature of both semantic and neologistic variants in jargonaphasia, and has been associated with jargonaphasia severity [8].…”
Section: Discussionmentioning
confidence: 99%